Drop hollows out the stone. How politicians and journalists experience harsh discourse and harassment online - Einarsdóttir, Bríet B.; Ólafsson, Jón Gunnar (Stjórnsýslustofnun, 2022)
The purpose of this study is to explore the views and experiences of politicians and journalists in Iceland regarding harsh discourse and harassment online. This type of discourse and harassment is prevalent in contemporary society and seen by many as an increasingly serious problem in the ever-changing landscape of media and politics, which involves changes in people’s interactions, for example on social media. The study sheds a light on the possible impact of such discourse and harassment, not only as regards the lives and work of politicians and journalists, but also on democracy itself. A qualitative study was conducted where individuals from both professions were interviewed, all of whom are prominent figures in Iceland. The interviews were thematically analyzed and methods of grounded theory used for drawing conclusions, which were then contextualized with relevant theories and research into social media and online harassment. The results revealed three main themes: social media as a double-edged sword, normalization of online harassment, and finally, the experiences, effects and consequences of such harassment. The interviewees’ perceptions of social media included both positive and negative attributes. Furthermore, their views and discussion were characterized by the normalization of online harassment, where it was not seen as a serious problem and instead considered a natural consequence of being a public figure. In regards to the experiences, effects and consequences of such harassment, clear signs of gender differences were found, both in its frequency, nature and severity. The impact of online harassment seemed to be more substantial among the participants than first appeared and the participants’ views on the subject became increasingly more serious as the interviews progressed. Markmið rannsóknarinnar er að kanna upplifun og viðhorf stjórnmála- og fjölmiðlafólks hérlendis af óvæginni umræðu og áreitni á netinu. Slík umræða og áreitni hefur verið áberandi að undanförnu og er af mörgum álitin ...